Paradigmas para o desenvolvimento: o papel histórico da CEPAL na interpretação da realidade Latino-Americana - Sgrignolli, Amanda (2022)
The Economic Commission for Latin America and the Caribbean (ECLAC), established over 70 years ago within the United Nations, played a key role as a school of thought for Latin American economic development in its first decades of existence, as it represented a thought of the region about its reality and its development, and lost relevance in the international scenario, mainly after the 1980s. The commission was established with the purpose of analyzing the economic, political and social trends in the region and characterized its own method of structural historical analysis, linked to international dynamics that places Latin America in relation to other nations and especially to developed nations. Its theoretical concepts can be classified into distinct phases, with key concepts elaborated in view of the changes in the international scenario that permeate the decades of these 70 years. In this context, the present research understands the historical relevance of ECLAC for Latin America and seeks to reconstruct its history and concepts in order to analyze Latin American development and the trajectory of the region's insertion in global capitalism. In this , the objective is to analyze the Commission and its theoretical framework regarding the development of Latin America over the decades and especially in the most recent scenario, in order to draw parallels, points of continuity and rupture in its analysis of the Latin American reality. , and changes in the region's thinking about these dynamics. The problem that guides the present research is how ECLAC thinking has changed in the face of economic development, and whether the changes in ECLAC thinking represent a break with the old political and economic molds of Latin America interpreted by ECLAC. The research results showed a weakening of the Commission in terms of influence on Latin American processes, as well as an approximation of its concepts to neoliberalism through neostructuralism, which seems to erase the structuralism based on the height of its thinking. This research seeks to address the research problem from the analysis of primary sources, such as ECLAC's official publications, and from secondary sources that situate ECLAC's Latin American developmental debate and its changes over the decades